Effects of parental separation on psychosocial well-being of children in secondary schools in Ibadan north local government, Ibadan, Oyo-State (2021)
The observation of a rise in separation cases raises a major concern of its effect on children at this particular developmental stage of life who are already facing very many changes happening in their life. Few studies have examined the effect of parental separation on psychosocial well-being of children among in-school teenagers in Nigeria. This study aimed to add to this body of literature by examining the effect of parental separation on social, spiritual, intellectual, psychosocial well-being on in-school teenagers in Ibadan North Local Government Area of Oyo State, Nigeria. The study adopted cross-sectional research design involving a sample of 400 in-school students in the study area using an adapted standardized validated instrument. Among other findings, it found a significant inverse relationship parental separation and psychosocial wellbeing among teenagers in Ibadan North LGA and almost half (42.4%) of the respondents who have separated parents have known about it for more ten years. This implies a teenagers who have the separated parents are more likely to experience ill-health psychosocially and these may also transcend to their intellectual well- being. Among others, policy makers should enact policy that mandate schools on the concurrent: assessment of students’ socio-demographics especially their parental status, their relationship and living condition periodically to continually evaluate social well-being, emotional well-being, and spiritual well-being. This will constantly help the teachers, school authorities, parent/guidance and other concerned bodies on the mental state of the students’ which is most necessary and determines their academic performance